Gambaran Kepatuhan Wajib Pajak UMKM Binaan KPP Kalideres - Kristanto, Septian Bayu; Olivia, Gabrille (Jurnal Buana Akuntansi, 2024)
Indonesia is one of the developing countries that is identical with development action activities from all types of industries, where the need for funds is sourced from the tax system collected from taxpayers. But in fact, not a few taxpayers are still not tax-compliant because they are influenced by some factors. The purpose of this research is to find out whether those factors influence MSMEs taxpayer compliance. The method that researchers use is qualitative-descriptive. The sample in this study is MSMEs that are doing business in the KPP Kalideres area, own or joint businesses, have an NPWP, and have a minimum turnover income of Rp.4,000,000,- and a maximum of Rp.500,000,000,-. The sampling technique uses a purposive sampling technique. Data collection techniques use interviews and documentation. The results of this study show the profile and background of MSME business actors, and fundamental factors such as the wealth of knowledge about taxation, the frequency and type of socialization used, effectiveness in modernizing the tax administration system, and the character of love of money attitudes are supporting factors for MSME business actors in influencing their mindset, decision making, and attitude in implementing their tax rights and obligations.